Governmental policies in Iraq between increasing rentier nature and weak economic diversification and their impact on economic stability for the during(2004-2018) - waely, Khudhair Abbas Hussein Al; Huzayran, Fahad Mghemish; Al zubaidi, Mohammed Naji Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
During the absence of good government policies in benefiting from the abundance of oil revenues in order to diversify the structure of gross domestic product and repair imbalances as well as diversify sources of income and exports and reduce the rate of economic openness, made the Iraqi economy a fragile, weak and unilateral economy in which oil represents the backbone of life, as well as the limited role of the private sector In economic activity, the dominance of the government sector, and the expansion of its consumer spending without developing a production base that excludes the Iraqi economy from rentier risks, as well as losing the ability to increase state resources from taxes and other non-oil exports, all of this will contribute to The economy faces constant problems due to the economy's dependence on external conditions and oil price shocks.The research reached a number of conclusions, the most important of which is the absence of government policies aimed at introducing economic reforms that reduce the impact of rentier nature, but there are some interim measures taken in times of low oil prices, as well as the lack of successive governments to benefit from large revenues in rebuilding the agricultural and industrial sectors Tourism and other sectors despite having great advantages.